Silvicultural, hydro-orological and economic aspects of a combination of vegetative (Falcataria moluccana-Vigna cylindrica) and terrace systems in soils of different slopes - Karyati Karyati; Sri Sarminah; Karmini Karmini; Rujehan Rujehan; Vebi Fitriana Eko Lestari; Wendy Satria Panorama (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Karyati, Sarminah S, Karmini, Rujehan, Lestari VFE, Panorama WS. 2019. Silvicultural, hydro-orological and economic aspects of a combination of vegetative (Falcataria moluccana-Vigna cylindrica) and terrace systems in soils of different slopes. Biodiversitas 20: xxxx. Soil and water conservation techniques involving a combination of vegetative and mechanical systems will increase the benefits from both conservation aspect as well as economic aspect. This study was aimed at analyzing the silvicultural, hydro-orological and economic aspects of a combination of vegetative (Falcataria moluccana-Vigna cylindrica) and terrace system in soils of different slopes (a steep and a very steep slope gradient). The silvicultural parameters examined in this study were the ground coverage of V. cylindrica growth and survival rate, stem diameter and height of F. moluccana trees. The hydro-orological parameters included erosion rate, erosion hazard index, erosion hazard class, and erosion hazard level. The economic parameters included total cost, total revenue, and profit. The result showed that the survival rate, diameter increment and height increment of F. moluccana, and ground coverage of V. cylindrica in the land with the steep slope (>25-45%) was 90%, 2.02 cm year-1, 1.54 m year-1, and 80-90%, respectively. The erosion rate, erosion hazard index, erosion hazard class, and erosion hazard level in this steep slope was 0.38 ton ha year-1, 0.03 (low), I (very low), and very low, respectively. In the steeper ground (>45%), the survival rate of F. moluccana reached 90%, the V. cylindrica coverage was 70-79% and the diameter and height increment of F. moluccana was 1.63 cm year-1 and 1.19 m year-1, respectively. The erosion rate was 1.81 ton ha-1 year-1, erosion hazard index of 0.13 (low), erosion hazard class was I (very low), and erosion hazard level was low in the very steep slope land. The profit from V. cylindrica was Rp 3,865,000.00 ha-1 cropping season-1 and Rp 665,000.00 ha-1 cropping season-1 in steep slope and very steep slope, respectively. The application of the proposed combination of vegetative and terrace system could reduce surface runoff and erosion rate in the long term, in addition to providing short term economic benefits.